Prediction of Chromatographic Separation of Eugenol by the Fast Fourier Transform Method - Wan Daud, Wan Ramli; Myint, San; Mohamad, Abu Bakar; Kadhum, Abdul Amir Hassan (Universiti Putra Malaysia Press, 2000)
The switching time to change from adsorption to desorption in liquid chromatography, which is the time at which the concentration of the effluent reaches the breakthrough value, is important in the operation, scale-up, and optimisation of chromatographic separation. The switching time can be estimated by computer simulation of the chromatographic adsorption column. In this paper, the theoretical simulation of the chromatographic column of Chen and Hsu (1987) based on the Fast Fourier Transform (FFT) method originally proposed for chromatographic systems by Hsu using estimated axial diffusivity, film mass transfer coefficient and pore diffusivity obtained from analytical scale separation, is compared with experimental data of chromatographic separation of eugenol. The use of FIT over more sophisticated techniques such as finite difference or orthogonal collocation methods was dictated by the simpler computation and the availability of better inverting techniques. The model was validated by experimental data on chromatographic separation of eugenol on IBondapak CIS analytical column, mobile phase methanol-water (80:20), and flow rate 0.5 ml/min, at different solution concentration injection at equilibrium condition. Physical property data required for validation such as equilibrium adsorption isotherm data was determined experimentally, and mass transfer data was calculated from normal correlations and from analytical scale separation. The simulation agreed with experimental data at a Peclet number of 6000, a bed length parameter of 3.0 and number of samples 90.